2022
DOI: 10.1111/ijn.13105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal breast‐feeding education on postnatal breast‐feeding fear in pregnant women in the COVID‐19 pandemic: A randomized clinical trial

Abstract: Aim This study aimed to investigate the effectiveness of prenatal breast‐feeding education provided to pregnant women who experience fear of breast‐feeding in the COVID‐19 pandemic period. Methods A prospective randomized controlled trial study was conducted with 128 pregnant women (64 in the experimental group and 64 in the control group) between November 2021 and February 2022. The data were collected via the Numeric Pain Rating Scale, the Breastfeeding Motivation Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
1
1
0
1
Order By: Relevance
“…breastfeeding more autonomously and avoid interference from external factors. This is in line with previous studies where SabancıBaransel et al (2023) found that breastfeeding health education during the COVID-19 pandemic significantly improved BMS scores and fostered positive maternal breastfeeding attitudes in the intervention group. In a study of validated factors of BM in primiparous women, it was shown that women who received breastfeeding support had higher levels of AM and were more willing to choose the breastfeeding option(Mizrak Sahin et al, 2019) than their peers who did not receive breastfeeding support.…”
supporting
confidence: 92%
“…breastfeeding more autonomously and avoid interference from external factors. This is in line with previous studies where SabancıBaransel et al (2023) found that breastfeeding health education during the COVID-19 pandemic significantly improved BMS scores and fostered positive maternal breastfeeding attitudes in the intervention group. In a study of validated factors of BM in primiparous women, it was shown that women who received breastfeeding support had higher levels of AM and were more willing to choose the breastfeeding option(Mizrak Sahin et al, 2019) than their peers who did not receive breastfeeding support.…”
supporting
confidence: 92%
“…This is the first study to highlight the lack of healthcare information and support in breastfeeding women with SARS-CoV-2 infection, and our results are in line with previously published data on non-infected women during the pandemic. In particular, Costantini et al demonstrated a significant reduction in healthcare support and advice for breastfeeding women during the pandemic [27], Ceulemans et al showed that 50% of included pregnant women reported less counseling on breastfeeding compared to before the pandemic [28], Lambelet et al showed that 47.5% of pregnant women and 36.2% of breastfeeding women reported the pandemic affected their interaction with healthcare services [29], while Barasel et al demonstrated that a prenatal breastfeeding education program increased the breastfeeding motivation and decreased fears of breastfeeding in a population of non-infected women during the COVID-19 pandemic [30]. When considering the impact of SARS-CoV-2 infection on the breastfeeding practice, our results are in contrast with reported data from Rani et al, who evaluated the type of breastfeeding in a cohort of infected women.…”
Section: Discussionmentioning
confidence: 99%
“…Por conseguinte, os impasses que interfiram nesse período consistem em ameaças profundas ao seu desenvolvimento biopsicossocial (BRASIL, 2018). Nesse ínterim, além de o sistema digestivo das crianças pequenas não estar habilitado para processar outros alimentos diferentes do leite materno antes dos 6 meses, a ausência ou a interrupção precoce do aleitamento materno exclusivo, contribui Brazilian Journal of Health Review, Curitiba, v. 7, n. 3, p. 01-23, may/jun., 2024 para o desenvolvimento de anemia, o que por sua vez pode contribuir para patologias ainda mais sérias (Flores, 2009;Sabanci Baransel;Uçar;Güney, 2023).…”
Section: Introductionunclassified